Los juegos de palabras para la compresión lectora en los niños y niñas de cuarto año paralelo “A”, de educación básica de la Unidad Educativa Juan de la Valle, cantón Riobamba, provincia de Chimborazo, año lectivo 2015-2016 - Paltán Soldado, Jimena Noemí (2016)
The research was conducted to determine the incidence of puns for reading comprehension in children Fourth Parallel Year "A", Basic Education, Education Unit Fiscal "Juan de Lavalle" canton Riobamba, Chimborazo province, school year 2015-2016, for which articulated the following specific objective; assess the level of reading comprehension; with what was clearly evident that a standard level of reading response is maintained; demonstrate the different puns as a methodological strategy in the development of reading comprehension; ludic elements like tongue twisters, jingles, jokes, highs and child guess generated in the complex mental process such as analysis, synthesis, abstract and sequential thinking to discover patterns, features and decipher clues or riddles posed by these activities; highlight the contribution of puns in reading comprehension as argumentative elements in the formation of concepts and in the process of learning new meanings .The methodological support research is the description of the variables in place of bone facts is a field study, which with debugging information the result was conclusive and could check the previously proposed hypothesis, determine the ludic literary resources should be considered as didactic and methodological strategy to get children significant levels of understanding and comprehension time to read and write findings, in structuring summaries, set main characteristics of the actors, characters in stories or stories.